2015
DOI: 10.1074/jbc.m114.611525
|View full text |Cite
|
Sign up to set email alerts
|

Human Liver Cytochrome P450 3A4 Ubiquitination

Abstract: Background: CYP3A4, a major human liver drug-metabolizing enzyme, is degraded upon phosphorylation and ubiquitination. Results: CYP3A4 phosphorylation occurs within negatively charged surface clusters that are important for electrostatic interactions with positively charged patches of the ubiquitination enzymes. Conclusion: These phosphorylated clusters enhance CYP3A4 molecular recognition by the ubiquitination complexes. Significance: This is the first mechanistic example of UBC7-gp78 substrate recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 91 publications
1
43
0
Order By: Relevance
“…However, the advent of much more sensitive LC-MS/MS methodology has led to the recognition that Ser129 is but one of 16 different CYP2E1 S/T-residues that are phosphorylated. Because CYP2E1 Ser129 mutation to Ala or Gly had little effect on its turnover upon transfection into COS 7 cells (Freeman & Wolf, 1994), we believe that some of these other 16 phosphorylated residues must be involved, as phosphorylation does indeed significantly enhance both CYP2E1 and CYP3A4 ERAD/UPD (Wang et al, 2009, 2011, 2012, 2015; Correia et al, 2014). Indeed, similar analyses of in vitro phosphorylated CYP3A4 revealed that PKA phosphorylates 5 Ser residues (S116, S119, S134, S259 and S478), whereas PKC phosphorylates 14 Ser/Thr residues (T92, S100, T103, S116, S119, S131, S134, T136, S139, S259, T264, T284, S398, S420).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, the advent of much more sensitive LC-MS/MS methodology has led to the recognition that Ser129 is but one of 16 different CYP2E1 S/T-residues that are phosphorylated. Because CYP2E1 Ser129 mutation to Ala or Gly had little effect on its turnover upon transfection into COS 7 cells (Freeman & Wolf, 1994), we believe that some of these other 16 phosphorylated residues must be involved, as phosphorylation does indeed significantly enhance both CYP2E1 and CYP3A4 ERAD/UPD (Wang et al, 2009, 2011, 2012, 2015; Correia et al, 2014). Indeed, similar analyses of in vitro phosphorylated CYP3A4 revealed that PKA phosphorylates 5 Ser residues (S116, S119, S134, S259 and S478), whereas PKC phosphorylates 14 Ser/Thr residues (T92, S100, T103, S116, S119, S131, S134, T136, S139, S259, T264, T284, S398, S420).…”
Section: Introductionmentioning
confidence: 97%
“…Such ERAD involves posttranslational phosphorylation of the P450 proteins by cytosolic kinases (Korsmeyer et al, 1999; Wang et al, 2001; Wang et al, 2009, 2011, 2012, 2015), their ubiquitination by the concerted action of the E1-Ub-activating enzyme, E2 Ub-conjugating enzyme/E3 Ub-ligase complexes (Morishima et al, 2005; Pabarcus et al, 2009; Wang et al, 2009, 2011, 2012, 2015; Kim et al, 2010), and subsequent degradation by the cytosolic 26S proteasome (Correia et al 1992b, 2005; Tierney et al, 1992; Roberts, 1997; Murray & Correia, 2001; Correia, 2003; Correia et al, 2005; Morishima et al, 2005; Liao et al, 2006; Correia & Liao, 2007; Faouzi et al, 2007; Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations